Technology transfer and the Internet: a chance for outsiders at public science to get into the business? - Dirk Czarnitzki; Christian Rammer (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2001)
The Internet is receiving increasing attention as a medium for technology transfer between public research and the enterprise sector. Based on a survey of public research units in natural sciences and engineering in Germany, we analyse the determinants of firm contacts established via the Internet. Special attention is paid to the effect of experiences in firm interaction in the past. Econometric estimation results suggest that Internet contact to firms is more likely to be established by public research units which are already well established in the transfer market. Research units which orientate their homepage design towards the business sector are more likely to build Internet-based contact with firms. There is no evidence that public research units which were market outsiders in the past use the Internet more intensively to get into the transfer business.
Keywords: O31; C35; L86; L14; 330; Technology transfer; Industry-science interaction; Internet use; Simultaneous equation Probit; Forschungskooperation; Internet; Technologietransfer; Wissenstransfer; Öffentliche Forschung; Schätzung; Deutschland